Menakar Manajemen Kinerja Guru Pendidikan Agama Islam - Aan Eko Khusni Ubaidillah (PROGRESSA: Journal of Islamic Religious Instruction, 2020)
Teacher performance is an urgent component in improving the quality of education, which will have an impact on the quality of human resources. The teaching performance of teachers not only affects the results of classroom learning activities, but also determines the future of the nation through investment in improving the quality (quality) of people. Poor teacher competence, of course, affects teacher performance that is not good enough in the world of education in Indonesia. This also happened to the Islamic Religious Education Teacher. The urgent role of teachers in improving the quality of human resources is considered not to be replaced by any great media. Therefore teachers play an important role in increasing the success of students, because teachers have the task of being the main implementer in the whole educational process.